2021
DOI: 10.1021/acs.jced.1c00345
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Correlation of the Solubility and Thermodynamic Properties of Ribavirin(II) in Nine Pure Solvents and (1-Propanol + Water) Binary Solvents

Abstract: The solubility of ribavirin(II) in nine pure solvents (formic acid, dimethyl sulfoxide, water, methanol, ethanol, 1propanol, 1-butanol, 2-butanol, and acetone) and a 1-propanol−water binary system was analyzed by a gravimetric method under atmospheric pressure and temperature ranging from 283.15 to 323.15 K. Experimental results show that when the temperature increases, the fractional solubility in all selected solvents also increases, and the dissolution behavior is affected by the solvent polarity. The solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…After five cycles, all the yields decrease significantly, and methyl oleate decreased the most, indicating that the catalytic stability of MIL-101-[IA-SO 3 H]­[HSO 4 ] in different kinds of polar solvents is different. Because the methanol, ethanol and propanol are obviously excessive, and the polarity followed by methanol > ethanol > propanol . It can be concluded that the stability of the immobilized sulfonic acid group functionalized ionic liquids showed negative correlation with the polarity of the system.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…After five cycles, all the yields decrease significantly, and methyl oleate decreased the most, indicating that the catalytic stability of MIL-101-[IA-SO 3 H]­[HSO 4 ] in different kinds of polar solvents is different. Because the methanol, ethanol and propanol are obviously excessive, and the polarity followed by methanol > ethanol > propanol . It can be concluded that the stability of the immobilized sulfonic acid group functionalized ionic liquids showed negative correlation with the polarity of the system.…”
Section: Resultsmentioning
confidence: 95%
“…Because the methanol, ethanol and propanol are obviously excessive, and the polarity followed by methanol > ethanol > propanol. 50 It can be concluded that the stability of the immobilized sulfonic acid group functionalized ionic liquids showed negative correlation with the polarity of the system.…”
Section: Synthesis Of Mil-101-[ia-so 3 H][hso 4 ] and Mil-101-[ia-coo...mentioning
confidence: 98%
“…Therefore, there exist other factors, including intermolecular interactions between solute and solvents and steric effects, that may affect the solubility. As shown in Figure , methyl 1,2,4-triazole-3-carboxylate has both an electron-withdrawing group (carboxyl) and an electron-donating group (amino), whose interactions with solvents may affect the solubility. For example, the high solubility of methyl 1,2,4-triazole-3-carboxylate in cyclohexanone may be explained by the “like dissolves like” rule as the carbonyl group coexisted in the methyl 1,2,4-triazole-3-carboxylate and cyclohexanone . The solubility sequence of methyl 1,2,4-triazole-3-carboxylate in acyclic ketone solvents may be mainly influenced by steric effects.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the high solubility of methyl 1,2,4-triazole-3-carboxylate in cyclohexanone may be explained by the "like dissolves like" rule as the carbonyl group coexisted in the methyl 1,2,4-triazole-3carboxylate and cyclohexanone. 27 The solubility sequence of methyl 1,2,4-triazole-3-carboxylate in acyclic ketone solvents may be mainly influenced by steric effects. The discordance between the order of solubility and the polarity of solvent in alcohol solvents may be caused by the interaction between solute and solvents.…”
Section: Yaws Modelmentioning
confidence: 99%
“…1-Propanol is extensively employed as an intermediate in several industries, materials science, and biological research fields, which is regarded as a key intermediate for propionic acid and isopropyl alcohol, and serves as a softener to enhance the product flexibility and resilience in the manufacturing processes of resins, rubber, and plastics. In addition, 1-propanol has been selected as a primary component ingredient in lubricants and coolants due to its high solubility and stability at low temperatures. Its significance in molecular biology, particularly in DNA precipitation, should not be underestimated. , The addition of 1-propanol alters the solution polarity, enabling DNA precipitation due to DNA’s negative charge in aqueous solutions. Given the widespread demand for 1-propanol in daily life, it was predominantly produced via the process of hydration–hydrogenation .…”
Section: Introductionmentioning
confidence: 99%